Dietary selenium peptide supplementation for increasing the growth of African catfish Clarias gariepinus - Muhammad Agus Suprayudi; Muhammad Roikhan Amanullah; Dedi Jusadi; Hasan Nasrullah; Ahmad Yazid Latif (Jurnal Akuakultur Indonesia)
Selenium is an essential micromineral that the body needs in modest amounts (0.2–12 mg/kg), yet it has important effects on the antioxidant defense, immune system, and digestive performance of aquatic species. This study aimed to analyze the growth of catfish (Clarias gariepinus) supplemented with feed additives containing selenium peptide through the coating method on feed. There were four different treatments, namely K (feed without feed additive), and feed with additive supplementation: A (3 g/kg feed), B (6 g/kg feed), and C (9 g/kg feed). A total of 15 catfish at an initial weight of 21.80 ± 0.29 g were reared in a 90×40×45 cm3 aquarium filled with water at a volume of 108 L, for 45 days. Fish were fed three times a day at satiation. Water quality management was carried out by the use of simple filtration in the container and water replacement to ensure optimum water quality values for catfish growth. The results showed that the final biomass of catfish fed with selenium peptide was significantly different (p<0.05) from catfish fed without selenium peptide, with a value of 1147,50 g and 96,67% of survival rate. Based on this study, the best dose of feed additive in catfish feed was 3 g/kg of feed.